Identification with the neighborhood: Discrimination and neighborhood size. Issue 5 (2nd September 2016) - Bernardo, Fátima; Palma-Oliveira, José-Manuel
Abstract: This paper analyzes the impact of a geographical social grouping (neighborhood) and its relative perceived size in the spontaneous group's identification level and place satisfaction, as well as the intensity of and motives for discrimination against inhabitants of other places. Two studies are presented: an experimental one using the minimal group categorization paradigm and an onsite investigation of a city neighborhood. Consistent with the predictions, the results showed that smaller neighborhoods reported higher identification and satisfaction with the place of residence, as well as higher discrimination of other neighborhoods. In line with the optimal distinctiveness theory (ODT), the findings showed that the motivation for discrimination varies as a function of the in-group size. Thus, the members of larger groups discriminate by increasing the differentiation between the in-group and the out-group, whereas the members of smaller groups increased the value of the in-group. Furthermore, the results were consistent with a social identity theory and ODT explanation of diverse research that shows the non-trivial nature of geographical bounded social grouping and its importance in a diverse set of contexts and its impact in inter-neighborhood relationships.